AAGBS brand ammbassador, paid Cardiff University a reciprocal visit - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2023)
YBhg. Dato' Seri Dr. Hj. Irmohizam Ibrahim, the AAGBS Brand Ammbassador, paid Cardiff University a reciprocal visit. Professor Rudolf Allemann, Pro-Vice Chancellor of International and Student Recruitment, who visited UiTM before on November 1, 2022, extended a warm welcome to him. Correspondingly, YBhg. Dato' Seri got the opportunity to visit Cardiff Business School (CARBS) and the Social Science Research Park (SPARK), as well as discussed any possible future collaborations between the two venerable universities. Also held over a great evening dinner with the International Office team, was a lengthy discussion regarding the MoU-related matters. Professor Dr. Norzanah Mat Nor from AAGBS UiTM who is currently on sabbatical at SPARK, Cardiff University, accompanied him during his fruitful visit. It is hoped that the proactive collaboration objectives would be successfully achieved, both by AAGBS, UiTM and Cardiff University.